Patient and staff experience with a new model of emergency department based mental health nursing care implemented in two rural settings. (July 2021) - Wand, Timothy; Collett, Gemma; Cutten, Alexa; Buchanan-Hagen, Sally; Stack, Amanda; White, Kathryn
Highlights: Providing effective mental health care in emergency departments is essential. Patients and staff reported on experiences with a mental health nurse service in two rural settings. Patients especially appreciated the prompt therapeutic care received. Staff valued a specialist on-site resource that improved emergency department service and care. Key principles of the model are potentially transferable to a range of emergency contexts. Abstract: Background: As part of a larger multi-site translational research project this study explored patient and staff experiences, perspectives and recommendations in relation to a mental health liaison nursing (MHLN) service implemented in the emergency department (ED) of two rural hospitals in New South Wales, Australia. Methods: Semi-structured interviews were conducted across the two sites with a sample of ED patients (n = 32), ED nurses (n = 14), ED medical officers (n = 11) and psychiatrists (n = 3). Data were analysed thematically. Findings: Patients highlighted the therapeutic benefits of the MHLNs, particularly being listened to and understood. Patients appreciated being seen promptly and having effective follow-up. Some negative experiences were encountered. Staff recognized that embedding the new model of care in the ED impacted positively on ED culture and practice. A nurse practitioner position as clinical lead instituted at one site made the most substantial contribution to integrating mental health care within the ED. Room for improvement was also noted. Conclusions: Findings from this study indicate that an ED-based model of MHLN care developed in a metropolitan setting was successfully translated to two rural EDs. While translating a model of care from one context to another is not without its challenges, adherence to the key principles of this model of MHLN care was associated with the most positive outcome.